Relationship of Coagulation Test Abnormalities to Tumour Burden and Postoperative DVT in Resected Colorectal Cancer - Iversen, L. H.; Thorlacius-Ussing, O. (Thrombosis and Haemostasis, 2002)
In a prospective study, coagulation test results were compared in 137 patients with colorectal cancer (CRC) and 39 subjects with benign colorectal diseases. Prothrombin fragment 1+2 (F1+2), thrombinantithrombin complex (TAT), and soluble fibrin (SF) were measured in plasma before and after surgery. CRC patients presented with significantly higher values of F1+2 and TAT than controls. Patients with localised CRC had elevated values of F1+2 and TAT, whereas patients with advanced CRC also had elevated SF values. TAT and SF levels correlated with tumour spread, and normal values virtually excluded advanced cancer. Postoperative deep venous thrombosis (DVT) was diagnosed by phlebography in 20% of the CRC patients. Preoperative values of the markers did not predict postoperative DVT, but postoperative values did.